The Prevalence and Severity of Sickle Cell Disease in Amravati District of Maharashtra - Ahmad, Maryam. M.; Gupta, H. N; Shinde, D.S.; Ruparel, N. D (Indian Journal of Pharmacy Practice)
Objective: The present study was undertaken to determine the prevalence and severity of Sickle Cell Disease among carriers and sufferers belonging to Amravati district. Methodology: Screening camps were held in different regions from which only positive groups of sickle cell solubility were considered for prevalence. A patient interview form was prepared with informed consent. The questionnaire was prepared with a view to collect data on the disease status of the sufferers only. Results: It was found that overall prevalence of sickle cell disease was 1% in the population mostly in SC, ST and Adivasi community (which represent economically backward population); more common in male gender. Age wise distribution of incidence of carriers was higher in adult age group while more sufferers were of the lower age group. Data regarding the prophylactic treatment impact revealed that patients receiving treatment had a successfully improved symptoms and an increase in the hemoglobin levels.
Keywords: Sickle cell disease; Haemoglobinopathies; Prevalence; Severity.